Hybrid introgression as a mechanism of rapid evolution and resilience to climate change in a riparian tree species - Ashlynn M. Hord; Dylan G. Fischer; Jennifer A. Schweitzer; Carri J. LeRoy; Thomas G. Whitham; Joseph K. Bailey (Communications Biology)
Abstract Determining whether organisms can undergo adaptive evolution at a pace commensurate with contemporary climate change is critical to understanding and predicting the consequences of such change. Hybrid introgression is a mechanism of rapid evolution by which species may adapt to climatic shifts. Here, we examine variation in growth and survival in a long-term common garden experiment with a foundation tree species to determine if introgression is enhancing climate change resilience. Two naturally hybridizing tree species, low elevation Populus fremontii and high elevation Populus angustifolia, and hybrid and backcross genotypes were planted in a low elevation, warm common garden. We show that P. angustifolia and backcross trees are vulnerable to warming, and their survival is related to climate and transfer distance (proxies for climate change). Increased odds of survival are associated with genetic introgression, as indicated by RFLP genetic markers. Thus, for these long-lived foundation trees, hybrid introgression is associated with increased resistance to selection pressures in warmer, drier climates. These data highlight the importance of evolutionary patterns and processes in shaping ecosystem responses to climate change. If adaptive introgression through hybrid zones is common, hybrid-specific conservation policies and restoration should be reconsidered in the context of global change.